Alterations of Erythrocytic Phosphorylated Alpha-Synuclein in Different Subtypes and Stages of Parkinson's Disease - Li, Xu-Ying; Li, Wei; Li, Xin; Li, Xu-Ran; Sun, Linjuan; Yang, Weiwei; Cai, Yanning; Chen, Zhigang; Wu, Jun; Wang, Chaodong; Yu, Shun (Frontiers in Aging Neuroscience, 2021)
Serine 129-phosphorylated alpha-synuclein (pS-α-syn) is a major form of α-syn relevant to the pathogenesis of Parkinson’s disease (PD), which has been recently detected in red blood cells (RBCs). However, alterations of RBC-derived pS-α-syn (pS-α-syn-RBC) in different subtypes and stages of PD remains to be investigated. In the present study, by using enzyme-linked immunosorbent assay to measure pS-α-syn-RBC, we demonstrated significantly higher levels of pS-α-syn-RBC in PD patients than in healthy controls. pS-α-syn-RBC separated the patients well from the controls, with a sensitivity of 93.39% (95% CI: 90.17%–95.81%), a specificity of 93.11% (95% CI: 89.85%–95.58%), and an AUC of 0.96. Considering motor subtypes, the levels of pS-α-syn-RBC were significantly higher in late-onset than young-onset PD (p=0.013) and in those with postural instability and gait difficulty than with tremor-dominant phenotype (p=0.029). In addition, the levels of pS-α-syn-RBC were also different in non-motor subtypes, which were significantly lower in patients with cognitive impairment (p=0.012) and olfactory loss (p=0.004) than in those without such symptoms. Moreover, the levels of pS-α-syn-RBC in PD patients were positively correlated with disease duration and Hoehn & Yahr stages (p for trend =0.02 and <0.001) as well as UPDRS III (R2=0.031, p=0.0042) and MoCA scores (R2=0.048, p=0.0004). The results obtained suggest that pS-α-syn-RBC can be used as a potential biomarker for not only separating PD patients from healthy controls but also predicting the subtypes and stages of PD.